STUDY GUIDE AND ACTION PLAN FROM SIRAT-UL-NABI صلى الله عليه وسلم TO SOLVE THE PROBLEM OF WATER SCARCITY IN PAKISTAN - Dr. Abdul Ghaffar; Muhammad Abdullah; Hafiz Intizar Ahmad (International Journal of Contemporary Issues in Social Sciences, 2024)
There are many reasons for water scarcity around the world such as decrease in rainfall, global warming, increasing demand for water and depletion of ground water etc. According to a survey, humans have extracted a huge amount of underground water. Groundwater in Texas and New Mexico is likely to dry up completely and in the northern states of America.The amount of groundwater is going down by 24 feet per year. The whole world is facing water shortage. The sources of water storage like dams and canals are also not the solution.